A multi‐country comparison of lower secondary students' critical thinking under the International Baccalaureate and national curricula - Johnston, S; McGrane, JA; Vendrell‐Morancho, M; Hopfenbeck, TN (Wiley, 2023)
Critical thinking is an essential skill for life-long learning, and, given its increasing importance as a graduate attribute, it is vital to evaluate how educational systems can best improve students' critical thinking through their curricula and classroom practices. This study evaluates the differences in the critical thinking skills of students in the International Baccalaureate (IB) Middle Years Programme (MYP), which explicitly emphasises critical thinking development in its curriculum and has been shown to facilitate classroom strategies to develop critical thinking, versus students enrolled in the national curricula in Australia, England and Norway. The study comprised 870 students across the MYP (n = 386) and non-MYP (n = 484) curricula in Grades 9 and 10 across 21 schools. Data were remotely collected on their critical thinking skills, and several other relevant cognitive, non-cognitive and background characteristics. A propensity score matching approach was used to match the MYP and non-MYP groups on these characteristics and their critical thinking skills were compared using weighted regression. Findings showed that, overall, MYP students possessed higher levels of critical thinking skills than their non-MYP peers with a moderate effect size (β = 0.38). This advantage also held at both grade levels and across Australian and English students, with no difference for Norwegian students. Thus, the MYP appears to be a promising exemplar for enhancing critical thinking among secondary-aged students, although context needs to be considered. Based on these findings, recommendations of specific instructional strategies are offered, as well as future research to inform criticalthinking pedagogy.